La palabra sensible: Herbert Marcuse, James Baldwin y Allen Ginsberg - Gatto, Ezequiel (2011)
Fil: Fil: Gatto, Ezequiel. Universidad Nacional de Rosario. Universidad de Buenos Aires. CONICET; Argentina